Opinions of Medan Area University Students on Men Who Use Skincare in The Communication Science Study Program - Panggabean, Gidion; Khairullah, Khairullah (Holistic Science, 2025)
Skincare is no longer exclusively for women, but is increasingly practiced by men, including among college students. However, public acceptance of this phenomenon remains mixed, particularly regarding long-entrenched masculinity norms. This study aims to explore the opinions of students at Medan Area University regarding men's skincare use, focusing on the factors influencing their perceptions. The research method used was exploratory qualitative research, with data collection techniques through in-depth interviews and participant observation of students in the Communication Studies Program. The results show that student opinions are divided into two main groups: those who accept skincare use by men as part of a healthy lifestyle, and those who still consider it contrary to traditional masculinity norms. Factors influencing student opinions include social media exposure, social environment, and individual gender constructs. Despite the growing trend of men's skincare, there is still resistance from certain groups who consider skincare unconventional to masculine identity. Therefore, broader education is needed to change public perception so that skincare can be accepted as a universal necessity, not just as an aesthetic.